2017
DOI: 10.1113/ep086167
|View full text |Cite
|
Sign up to set email alerts
|

LunHab: interactive effects of a 10 day sustained exposure to hypoxia and bedrest on aerobic exercise capacity in male lowlanders

Abstract: What is the central question of this study? What are the distinct and interactive effects of a 10 day exposure to hypoxia and horizontal bedrest on the whole-body peak oxygen uptake and on the regional cerebral and skeletal muscle tissue oxygenation during upright cycle ergometry in male lowlanders? What is the main finding and its importance? A 10 day sustained exposure to hypoxia aggravates the bedrest-induced reduction in peak oxygen uptake during dynamic exercise engaging large muscle groups, but mitigates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This finding is in line with the results from other investigations, wherein the post-bedrest exercise provocation was conducted at a fixed absolute intensity (Greenleaf & Reese, 1980;Lee et al, 2002). The response appeared to be independent of any bedrest-related variation in the rate of heat production, judging by the similarV O 2 and H prod values attained in the PRE and POST-A trials, an observation that indeed is consistent with that reported in other bedrest studies (Convertino, 1996;Greenleaf & Reese, 1980;Keramidas et al, 2017;Lee et al, 2002). Still the 35 days of bedrest diminished the restingT sk by ∼1.5 • C and blunted the exercise-induced increase inT sk .…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with the results from other investigations, wherein the post-bedrest exercise provocation was conducted at a fixed absolute intensity (Greenleaf & Reese, 1980;Lee et al, 2002). The response appeared to be independent of any bedrest-related variation in the rate of heat production, judging by the similarV O 2 and H prod values attained in the PRE and POST-A trials, an observation that indeed is consistent with that reported in other bedrest studies (Convertino, 1996;Greenleaf & Reese, 1980;Keramidas et al, 2017;Lee et al, 2002). Still the 35 days of bedrest diminished the restingT sk by ∼1.5 • C and blunted the exercise-induced increase inT sk .…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we opted for running the performance tests as soon as possible following the cessation of the hypoxic acclimatization. The timing of the exercise trials following hypoxic acclimatization could have also benefited V O 2max in NOR and HE (33). This hypothesis is supported by the fact that all the NOR and most of the HE trials were conducted on the second and third day post acclimatization when plasma volume is recovering (21).…”
Section: Consequences Of Hypoxic Acclimatizationmentioning
confidence: 87%
“…Other ground‐based platforms have also specifically looked at physiological and psychological alterations induced by a changing environment, e.g. by conducting bedrest studies in hypoxic environments (PlanHab and Lunhab studies; Ciuha, Eiken, & Mekjavic, 2015; Keramidas, Mekjavic, & Eiken, 2017; McDonnell, Eiken, Frings‐Meuthen, Rittweger, & Mekjavic, 2019; Rullman, Mekjavic, Fischer, & Eiken, 2016; Salvadego et al., 2018; Šket et al., 2017; Strewe et al., 2017, 2018a). The ESA aims to further build upon this in the future and has initiated preparations for a 60‐day head down tilt bedrest study at the Planica Nordic Centre in Slovenia, allowing environmental pressure and oxygen parameters to be altered.…”
Section: Discussionmentioning
confidence: 99%